A study of behavioral and emotional changes in stress that can affect academic performance of Universiti Malaysia Sarawak students - Atiqah, binti Musa (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study investigates ifthe changes of behavior and emotion in stress ofUniversiti Malaysia Sarawak (UNIMAS) students can affect their academic performance. Students tend to encounter stress during study. Using the changes of behavior and emotion in stress, researcher emphasized what factor affect students' academic performance the most. The results assist students on how to improve academic performance using stress as a booster. Quantitative method approach was implemented by selecting undergraduate students as participants for this study. Questionnaires on Perceived Stress Scale, Problem Behavior and Emotional Regulation Test were randomly distributed and the data collected was analyzed. Based on Pearson Correlation Coefficient results, there are small negative correlations between behavioral changes in stress and student academic performances. Meanwhile, there are no relationship between emotional changes in stress and students' academic performances. Furthermore, the Multiple Regression result shows that behavioral changes in stress was the dominant factor that affected academic performance of UNIMAS students. This study highlighted the effect of behavioral changes in stress that affected academic performance of UNIMAS students. In a nutshell, students should improve their behavior in order to achieve better academic results.